2019
DOI: 10.1002/dta.2689
|View full text |Cite
|
Sign up to set email alerts
|

Detection of testosterone doping in female athletes

Abstract: Testosterone doping remains a prevalent and potent form of drug cheating among elite athletes. In men, the urine testosterone (T) to epitestosterone (E) ratio (T/E ratio) can identify administration of exogenous T by its suppression of endogenous T production through strong negative feedback on endogenous T and E production as well as spill over into urine of extra testosterone. However, this mechanism may be partially inoperative in females whose much lower circulating T derives from three sources, none subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 29 publications
5
56
1
Order By: Relevance
“…The results indicated that dermal testosterone use in women is not detectable with the traditional T/E biomarker, despite supra‐physiological total testosterone serum concentrations. This is in line with a recent publication showing that elevated serum testosterone concentrations in two elite female athletes did not result in elevated urinary T/E ratios in their ABPs . Since our study and the study conducted by Handelsman et al are both based on case observations, there is an urgent need to perform a controlled study in relation to transdermal testosterone administration in women.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results indicated that dermal testosterone use in women is not detectable with the traditional T/E biomarker, despite supra‐physiological total testosterone serum concentrations. This is in line with a recent publication showing that elevated serum testosterone concentrations in two elite female athletes did not result in elevated urinary T/E ratios in their ABPs . Since our study and the study conducted by Handelsman et al are both based on case observations, there is an urgent need to perform a controlled study in relation to transdermal testosterone administration in women.…”
Section: Discussionsupporting
confidence: 91%
“…This is in line with a recent publication showing that elevated serum testosterone concentrations in two elite female athletes did not result in elevated urinary T/E ratios in their ABPs. 12 Since our study and the study conducted by Handelsman et al are both based on case observations, there is an urgent need to perform a controlled study in relation to transdermal testosterone administration in women. It is possible that longitudinal monitoring of the ABP biomarkers in our participants rather than single urine sampling would have resulted in atypical findings.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Today the ABP includes a steroidal and a hematological module, of which the former includes the urinary concentrations of six steroid metabolites. The monitoring of the circulatory levels of steroids, especially testosterone (T) and dihydrotestosterone (DHT) has been suggested to enhance the sensitivity of detecting endogenous anabolic androgenic steroids 9,10 . The hematological ABP module includes parameters such as the reticulocyte percentage (RET%), hemoglobin (HGB), and an OFF‐score to determine whether blood doping or tampering with the blood has occurred 11,12 …”
Section: Introductionmentioning
confidence: 99%